Assessing English coursebooks for young learners: A critical analysis using Tomlinson's framework - Maidari, Siti Raudhah (Accentia: Journal of English Language and Education, 2025)
This study evaluates an English coursebook for young learners, My Next Words, using Tomlinson’s (2011) framework, which emphasizes meaningful input, engagement, affective involvement, and learner autonomy. The analysis focuses on the coursebook's ability to align with young learners’ developmental needs, cognitive processes, and social interactions. Findings reveal that the coursebook excels in engaging learners through repetitive activities, songs, and colorful illustrations that support vocabulary retention. However, limitations were identified in areas such as personalization, cultural inclusivity, and opportunities for learner autonomy. The lack of open-ended tasks and minimal scaffolding in grammar activities restricts learners’ ability to explore language creatively. Additionally, the coursebook assumes a uniform classroom context, which reduces its applicability across diverse cultural settings. Recommendations include incorporating more scaffolded tasks, integrating culturally inclusive content, and designing activities that foster personalization and learner autonomy. By addressing these gaps, My Next Words could better support young learners' language acquisition and align with both developmental and pedagogical principles. This research contributes valuable insights into the evaluation and development of effective EYL coursebooks that cater to holistic language learning needs.